Dewan Komisaris Independen, Komite Audit, Koneksi Politik dan Tax Avoidance - Karuniasari, Lidia Ayu; Noviari, Naniek (E-Jurnal Akuntansi, 2022)
Tax avoidance is an act of minimizing the tax burden by taking advantage of the loopholes in the applicable tax regulations. This study examines the effect of independent commissioners, audit committees and political connections on tax avoidance. The research sample is Property and Real Estate Companies listed on the IDX in 2018-2020. Determination of the sample using purposive sampling method and produced 54 observations. The results showed that the independent board of commissioners had no effect on tax avoidance. the audit committee has a negative effect on tax avoidance and political connections have no effect on tax avoidance. Keywords: Independent Board of Commissioners; Audit Committee; Political Connection; Tax Avoidance .